Enhancing phase I dose-finding trials design through dynamic borrowing information and handling late-onset toxicity - Yang, Wenyun; He, Ruyue; Sun, Yuehan; Yan, Fangrong; Wang, Fei (Frontiers in Pharmacology, 2023)
In recent years, there has been a growing trend among regulatory agencies to consider the use of historical controls in clinical trials as a means of improving the efficiency of trial design. In this paper, to enhance the statistical operating characteristic of phase IPhase I dose-finding trials, we propose a novel model-assisted design method named "MEM-Keyboard" based on the multisource exchangeability models (MEMs) that allow for dynamic borrowing of information from multiple supplemental data sources, including historical trial data, to inform the dose-escalation process. Furthermore, with the frequent occurrence of delayed toxicity in novel anti-cancer drugs, we extended our proposed method to handle late-onset toxicity by incorporating historical data. This extended method is referred to as "MEM-TITE-Keyboard" and aims to improve the efficiency of early clinical trials. Simulation studies have indicated that the proposed methods can improve the probability of correctly selecting the maximum tolerated dose (MTD) with an acceptable level of risk, compared to designs that do not account for information borrowing and late-onset toxicity.